Transformasi Program Makan Bergizi Gratis sebagai Strategi Pembangunan Ekonomi Inklusif Berbasis Sumber Daya Lokal Pedesaan - Nur Solikin; Linawati (Commodities, Journal of Economic and Business, 2026)
The Free Nutritious Meals (MBG) program not only aims to improve the nutritional status of the community but also has the potential to become an inclusive economic development strategy based on local rural resources. This article aims to analyze the potential for MBG transformation through strengthening the agribusiness value chain, the economic multiplier effect, and local institutions. This research uses a literature review method by examining various scientific articles, policy documents, and relevant reports. The analysis is conducted through three approaches: an agribusiness value chain analysis to identify the relationship between food supply and rural economic activities, an economic multiplier effect analysis to assess the impact of increasing food demand on the community's economy, and an institutional analysis to identify the role of farmer groups, livestock groups, cooperatives, Village-Owned Enterprises (BUMDes), and food MSMEs in supporting program implementation. The results of the study indicate that MBG can strengthen the linkages between the agricultural, livestock, food processing, and distribution sectors through the utilization of local resources. Increased demand for local food has the potential to increase community income, expand employment opportunities, and encourage rural economic growth. The program's success is also influenced by the strengthening of local institutions as managers of the food supply chain. Thus, MBG can be a development strategy that not only improves the nutritional quality of the community, but also strengthens the rural economy in an inclusive and sustainable.